Perencanaan Pembelajaran Pendidikan Agama Islam Sebagai Upaya Peningkatan Mutu Pembelajaran - Rachman, Fathor (AL-WIJDÃN Journal of Islamic Education Studies, 2018)
Abstract Learning planning is the process of making decisions on the results of rational thinking about specific learning goals and objectives, namely changes in behavior and a series of activities that should be carried out as an effort to achieve these objectives by utilizing all potential and existing learning resources. Scientific learning is student-centered learning, where students are required to find material related to certain subjects themselves. There are 5 scientific learning steps, namely: observing, asking, experimenting, associating / processing information / reasoning, and communicating. The implementation of learning planning manifested in the form of a learning plan can be made for one year called the annual program, in one semester called the semester and daily program called the learning unit program. Keywords: Planning methods, Scientific learning, Quality.